Dynamic path tracking control of a vehicle on slippery terrain. (September 2015) - Lucet, Eric; Lenain, Roland; Grand, Christophe
Abstract: This paper deals with accuracy and reliability for the path tracking control of a four wheel mobile robot with a double-steering system when moving at high dynamics on a slippery surface. An extended kinematic model of the robot is developed considering the effects of wheel–ground skidding. This bicycle type model is augmented to form a dynamic model that considers an actuation of the four wheels. Based on the extended kinematic model, an adaptive and predictive controller for the path tracking is developed to drive the wheels front and rear steering angles. The resulting control law is combined with a stabilization algorithm of the yaw motion which modulates the actuation torque of each four wheels, on the basis of the robot dynamic model. The global control architecture is experimentally evaluated on a wet grass slippery terrain, with speeds up to 7 m/s. Experimental results demonstrate enhancement of tracking performances in terms of stability and accuracy relative to the kinematic control. Abstract : Highlights: Extended kinematic and dynamic models of a double-steered vehicle are proposed. A new adaptation dynamic sideslip observer considers the lateral slope. An adaptive and predictive double steering controller is developed. A stabilizer of the yaw motion modulates the actuation torque of each four wheels. Experiments are performed on a wet grass slippery terrain, with speeds up to 7 m/s.